Indexation of Fixed-Income Portfolios to the IMA-B - Emilio Ricardo Carvalhais; Antonio Marcos Duarte Júnior (BBR: Brazilian Business Review)
This study considers the problem of indexing fixed-income portfolios to the ANBIMA Market Index – Series B (IMA-B), composed of Brazilian National Treasury Notes – Series B (NTNBs). We propose a mathematical model that minimizes the deviations of the returns of the chosen portfolio in relation to the returns of the index’s theoretical portfolio. The resulting model is a mathematical programming problem with convex objective function, linear constraints and free and non-negative integer variables. Five numerical examples with real data are presented to illustrate the model’s practical use. The results obtained from the fits are analyzed together with data for funds indexed to the IMA-B existing in the Brazilian financial market. The proposed method resulted in fits with optimal control of the tracking errors of the indexed portfolio.